Vertical stratification of an avian community in New Guinean tropical rainforest - Chmel, Kryštof; Riegert, Jan; Paul, Luda; Novotný, Vojtěch (Population ecology, 2016)
Vertical stratification of avian communities has been studied in both temperate and tropical forests; however, the majority of studies used ground-based methods. In this study we used ground-to-canopy mist nets to collect detailed data on vertical bird distribution in primary rain forest in Wanang Conservation Area in Papua New Guinea (Madang Province). In total 850 birds from 86 species were caught. Bird abundance was highest in the canopy followed by the understory and lowest in the midstory. Overall bird diversity increased towards the canopy zone. Insectivorous birds represented the most abundant and species-rich trophic guild and their abundances decreased from the ground to canopy. The highest diversity of frugivorous and omnivorous birds was confined to higher vertical strata. Insectivorous birds did not show any pattern of diversity along the vertical gradient. Further, insectivores preferred strata with thick vegetation, while abundance and diversity of frugivores increased with decreasing foliage density. Our ground-to-canopy (0–27 m) mist netting, when compared to standard ground mist netting (0–3 m), greatly improved bird diversity assessment and revealed interesting patterns of avian community stratification along vertical forest strata.